The Long and Winding Road of Enterprise System Implementation: Finding Success or Failure?. Issue 2 (November 2015) - Grainger, Nick; McKay, Judy
A global manufacturing company needing to upgrade its IT to support rapid growth decided to pilot an enterprise system (ES) implementation in one of its European businesses. This was unsuccessful, but a second attempt in Australia, drawing on the many lessons learnt was regarded as successful. Subsequently, 14 implementations proceeded all over the Asia Pacific region and elsewhere in Europe with excellent outcomes. But the next implementation of the ES into a recently acquired business in New Zealand (NZ) proved problematic. The NZ management team and users were highly critical of the system and appeared to strongly resist its implementation. Cutover was eventually mandated and did occur, but the business almost failed because of problems with the new system. Following months of complaints and lobbying, the CIO in Head Office dispatched a small experienced team to NZ to review the situation. This case raises two fundamental challenges of IT management. It supports discussion of the many issues associated with the implementation of new systems and technologies, deepening appreciation of the challenges (particularly social, cultural and political) of IT implementation. It also supports learning about the phenomenon of resistance to change in the context of IT implementation. 1